Solar assisted multi-generation system using nanofluids: A comparative analysis - Abid, Muhammad; Ratlamwala, Tahir A. H.; Atikol, Ugur (Pergamon-Elsevier Science Ltd, 2017)
In this comparative study, a parabolic trough solar collector and a parabolic dish solar collector integrated separately with a Rankine cycle and an electrolyzer are analyzed for power as well as hydrogen production. The absorption fluids used in the solar collectors are Al2O3 and Fe2O3 based nanofluids and molten salts of LiCl RbCl and NaNO3-KNO3. The ambient temperature, inlet temperature, solar irradiance and percentage of nanoparticles are varied to investigate their effects on heat rate and net power produced, the outlet temperature of the solar receiver, overall energy and exergy efficiencies and the rate of hydrogen produced. The results obtained show that the net power produced by the parabolic dish assisted thermal power plant is higher (2.48 kW-8.17 kW) in comparison to parabolic trough (1 kW-6.23 kW). It is observed that both aluminum oxide (Al2O3) and ferric oxide (Fe2O3) based nanofluids have better overall performance and generate higher net power as compared to the molten salts. An increase in inlet temperature is observed to decrease the hydrogen production rate. The rate of hydrogen production is found to be higher using nanofluids as solar absorbers. The hydrogen production rate for parabolic dish thermal power plant and parabolic trough thermal power plant varies from 0.0098 g/s to 0.0322 g/s and from 0.00395 g/s to 0.02454 g/s, respectively. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
8th International Exergy, Energy and Environment Symposium (IEEES) -- MAY 01-04, 2016 -- Antalya, TURKEY
Keywords: Exergy; Nanofluids; Parabolic trough; Parabolic dish; Hydrogen production; Multi-generation